Reconstruction of Legal Protection for Civil Servants as Whistleblowers in Eradicating Corruption Crimes in Indonesia - Austin Al Hariz; Hibnu Nugroho; Ridwan Ridwan (Journal of Law and Legal Reform, 2024)
Corruption in Indonesia remains a pervasive and deeply entrenched issue, severely undermining public trust, hindering development, and destabilizing governance. Addressing corruption requires robust mechanisms, especially the protection of whistleblowers—particularly civil servants (Aparatur Sipil Negara, ASN)—who play a critical role in exposing corruption within public institutions. However, ASN whistleblowers face significant challenges, including retaliation, lack of legal protections, insufficient reporting channels, and limited incentives, which hinder their effectiveness and deter reporting. This study investigates the existing legal frameworks for protecting ASN whistleblowers, assessing their implementation and effectiveness, and proposing necessary reforms. Through qualitative legal research, including primary and secondary legal materials and interviews with key informants, the research identifies significant shortcomings in Indonesia's whistleblower protection laws. These gaps—such as inadequate safeguards, procedural inefficiencies, and limited institutional support—expose whistleblowers to retaliation, weakening anti-corruption efforts. The findings emphasize the urgent need for comprehensive legal reforms to enhance whistleblower protection, ensuring their safety, security, and empowerment. By filling this critical gap, the study contributes to strengthening Indonesia’s anti-corruption initiatives and highlights the essential role of whistleblowers in fostering transparency and accountability. This research calls for policymakers to prioritize whistleblower protection as a core component of the nation’s anti- corruption strategy, offering actionable recommendations to improve legal frameworks and institutional support. In doing so, it underscores the need for urgent reforms to combat corruption and promote a culture of accountability in Indonesia’s public sector.